Milk pasteurizer for the elaboration of sour cream (2019)
The pasteurization process consists on heating liquids until a temperature that allows the elimination of pathogenic microorganisms, and in this way, extend the shelf life of the product. The automatic milk pasteurization prototype as the first stage in the production line of sour cream is a contribution for small producers who make sour cream from raw milk, which by established regulations in matters of health and safety have been affected in the commercialization and sale of products that do not comply with the required technical specifications. The objective of this work was to design and build a slow pasteurizing equipment. The prototype was equipped with an agitator motor, solid state temperature sensors (LM35), ultrasonic level sensor (SRF05), control system and system of visualization of the responses emitted by the devices.